DOP08 The regulatory landscape of intestinal cells—investigating the transcriptional effect of autophagy impairment observed in Crohn's disease using organoid and network biology approaches. (25th January 2019) - Treveil, A; Sudhakar, P; Matthews, Z; Wrzesinkski, T; Jones, E; Powell, P; Wileman, T; Hautefort, I; Hall, L; Di Palma, F; Haerty, W; Korcsmaros, T
Abstract: Background: Intestinal homeostasis is maintained through complex interactions between the epithelial cell barrier, the host immune system, and the enteric microbiota. Paneth cells of the small intestinal crypts play an important role in innate immunity through release of antimicrobial peptides (AMPs). AMP release depends on the intracellular recycling process autophagy, and dysfunction of both of these processes, in Paneth cells, has been shown to contribute to Crohn's disease. Therefore, we have developed an integrative workflow to study regulatory pathways of intestinal cells such as Paneth cells, using organoids and network biology. We have applied this pipeline to study potential master regulators of Paneth cells and to analyse the regulatory effect of autophagy impairment using an extreme Crohn's disease model. Methods: We performed detailed transcriptomics analysis on differentiated organoids derived from normal mice and mice deficient in the autophagy-related protein Atg16l1. These organoids were grown from isolated small intestinal crypts, where the Lgr5+ stem cells drove multi-lineage differentiation to form the in vivo architecture of the epithelial layer. Application of a certain cocktail of growth factors drives the differentiation towards Paneth cells, enriching for Paneth cells compared with the control organoids. Differentially expressed mRNAs, miRNAs and long non-coding RNAs were identified by comparing RNA expression between the organoids. These RNAs were contextualised by linking them together into a unified regulatory network. This network was generated using experimental information from published databases such as GTRD and TarBase. Results: By mapping cell-type–specific marker genes to the network derived from normal mice, we were able to identify regulators potentially contributing to Paneth cell–specific functions. Among the seven putative master regulators, we identified four nuclear hormone receptors with links to inflammatory bowel disease (IBD), immunity, and autophagy: Vdr, Rxra, Nr1d1, and Nr3c1 . Subsequent analysis of the autophagy impaired mouse-derived networks has enabled investigation of the effect of autophagy impairment on the regulatory landscape of Paneth cell. Conclusions: We have developed an integrative -omics and multi-layered network approach to study regulatory landscapes of small intestinal cells using organoids. We show that application of these methods in a cell-type specific context can be used to disentangle multi-factorial mechanisms in Crohn's disease. The established workflow will enable analysing human Paneth cells from clinical biopsies as well as use to investigate the regulatory effect of microbial challenges on Paneth cells in Crohn's disease.